A longitudinal research on moderating effect of leader-member exchange on the relationships between leadership styles and job performance. (1st January 2013) - Akkoç, İrfan; Altay, Melih; Turunç, Ömer
The subject of that study is the moderating effect of leader-member exchange on the relationship between leadership styles and job performance. The research is performed as longitudinal on 254 persons working in software firms established in Ankara (Turkey). It is defined according to the research results that the relationship-oriented and task-oriented leadership behaviours have effect on the job performances of the employees. In addition, it is determined that the quality of the leader-member exchange has a moderating effect on the relationship between the leadership styles and job performance.